Impact of Multiple Daily Clinical Pharmacist-Enforced Assessments on Time in Target Sedation Range. (October 2018) - Lizza, Bryan D.; Jagow, Benjamin; Hensler, David; Cooper, Craig J.; Short, Elizabeth J.; Maas, Matthew B.; Naidech, Andrew M.; Wunderink, Richard G.
Objectives: Incorporation of a single daily assessment by a clinical pharmacist to improve adherence with a sedation protocol is associated with reduced duration of mechanical ventilation and intensive care unit (ICU) length of stay (LOS). We test the feasibility of incorporating a clinical pharmacist into more frequent sedation assessments and observed whether there are any potential differences in the sedatives administered. Methods: Prospective, quasi-experimental, pilot study of patients admitted to the medical ICU. Patients were included in the analysis if ≥18 years of age within the first 24 hours of initiation of mechanical ventilation. Our primary intent was to test the clinical feasibility surrounding more frequent sedation assessments by a clinical pharmacist by evaluating potential differences in time in target sedation range and sedative administration. Exploratory efficacy end points included time in target sedation range (0 to −2) using the Richmond Agitation Sedation Scale (RASS) and sedative exposure. Patients were assigned to receive either 3 assessments with a clinical pharmacist per day (intervention) or a single assessment by a clinical pharmacist per day (standard of care). During the assessments, clinical pharmacists participated in the RASS administration and made dosing adjustments according to an established sedation protocol. Main Results: Seventeen patients were enrolled (n = 6 intervention group, n = 11 standard of care). Duration of mechanical ventilation was similar in the 2 groups (intervention 100.0 hours [52.5-197.5] vs control 76.0 hours [46.0-201.0], P = .95), but patients in the intervention group exhibited a greater percentage time in the target RASS range (intervention 76.0% [53.7-81.5%] vs control 45.2% [35.3-67.0], P = .11) that was not statistically significant. Patients in the intervention group received less fentanyl per day (820.9 µg [227.3-1579.4] vs 1997 µg [1648.2-2477.2], P = .02) than in the control group. Conclusion: Incorporating a clinical pharmacist into more frequent daily sedation assessments was associated with a reduction in fentanyl administration. There were no observed differences in time in target sedation range or reduction in duration of mechanical ventilation.